A escritura desejante de Hilda Hilst - Pereira, Ana Paula de Oliveira (2006)
Acting on poetry, on prose and on drama through forty years, Hilda Hilst erected a singular discourse which thematic bases are God, Love and Death. The following assignment has as purpose to reflect and analyze the poetic constructions of the eroticism in the Hilstian poetry, according to the point of view of the literary criticism, considering the philosophy and the psychoanalysis contributions. The hypothesis that supports this research has its source in the knowledge of the philosopher Georges Bataille (continuity x being discontinuity) and leans on the mutual interweaving proposed by Octavio Paz (the eroticism as a bodily poetic , and the poetry as verbal erotic ). As a result, it was concluded that the Hilstian poetry carries out the fusion of eroticism and literary creation